Longitudinal changes in the rate of force development during single-leg press and sports performance for jumpers - Zushi, K.; Kariyama, Y.; Ogata, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2020)
The aim of this study was to investigate longitudinal changes in rate for development (RFD) during the early, late, and whole phases, and to determine whether early RFD is exhibited in response to the improvement of explosive force production in training throughout the competitive season. Fifteen male jumpers participated in personal training according to the training cycle (Semi-annual two-cycle periodization model) of their team. The early, late and average RFD along with peak force during isometric single-leg press with a knee angle of 115° were measured. The measurement was performed during the pre-season (January or March) and post-season (September or November). Based on comparison between the two measurements, it was found that 10 participants displayed improved performance in the major jump event. The average RFD increased significantly for all participants (p = 0.02, d = 0.67). Participants who achieved their personal best had seen a significant increase in early RFD (p = 0.03, d = 0.84). In the contrast, late RFD (all participants; p = 0.06, d = 0.54, participants who achieved personal best; p = 0.07, d = 0.65) and peak force (all participants; p = 0.31, d = 0.27, participants who achieved personal best; p = 0.15, d = 0.50) did not show significant changes. These results suggested that changes in early, late, and average RFD varied respectively. Moreover, early RFD was found to be the best indicator that reflects improved jumping performance through explosive force production compared to late RFD, average RFD, and peak force.